Agricultural diversity and food security data curation for low- and middle income countries in Africa, Asia and the Americas - Waha, Katharina; Francesco, Accatino; Cecile, Godde; Cyrille, Rigolot; Jessica, Bogard; Joao Pedro, Domingues; Gotor Facello, Elisabetta; Herrero, Mario; Guillaume, Martin; Mason-D'Croz, Daniel; Francesco, Tacconi; Wijk, Mark T. van (2023)
The data set includes data from 88 research articles that have assessed the direction and magnitude of the association between an indicator of agricultural diversity at farm-, regional-, or national-level and an indicator of food security. This is the data set created as part of the review article: Waha et al. (2022): The benefits and trade-offs of agricultural diversity for food security in low- and middle-income countries: A review of existing knowledge and evidence. Global Food Security 33, 100645. https://doi.org/10.1016/j.gfs.2022.100645 (2023-02-23)